Iowa Birdline update, November 14, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for November 14, 1988. Highlights of the update include several excellent sightings from around the state, including a Pine Grosbeak, a Lesser Black-backed Gull, Greater Scaup, two Golden Eagles, and as many as 1000 Tundra Swans. Also of note was the continued presence of a Rock Wren as well as the first Snowy Owl sighting of the season. Epson - sheet feed